Thermoplastic elastomer resin composition and molded body

JP2025031636APending Publication Date: 2025-03-07TORAY CELANESE CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024138897
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-08-25
Filing Date
2024-08-20
Publication Date
2025-03-07

AI Technical Summary

Benefits of technology

【0015】 本発明によれば、柔軟で透明性に優れ、良触感で外観に優れる熱可塑性エラストマ樹脂組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031636000001
    Figure 2025031636000001
  • Figure 2025031636000002
    Figure 2025031636000002
  • Figure 2025031636000003
    Figure 2025031636000003
Patent Text Reader

Abstract

To provide a thermoplastic elastomer resin composition which is flexible and has excellent transparency, and has good texture and excellent appearance.SOLUTION: A thermoplastic elastomer resin composition contains 0.01 to 3 pts.mass of an alkali metal salt (C) of a carboxylic acid and / or 0.2 to 20 pts.mass of an ethylene copolymer (D) having a carboxylic acid metal base at its side chain, with respect to 100 pts.mass of the total of 10 to 95 mass% of a polyester block copolymer (A) containing 10 to 50 mass% of a high melting point crystalline polymer segment (a) composed of a crystalline aromatic polyester unit and 90 to 50 mass% of a low melting point polymer segment (b) composed of an aliphatic polyether unit and / or an aliphatic polyester unit, as main components and 90 to 5 mass% of a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt.% or less, and has a haze value (cloudiness) measured by a sheet having a thickness of 2 mm of 60% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermoplastic elastomer resin composition which is flexible, has excellent transparency, a good feel and an excellent appearance, and to a molded article thereof. [Background technology]

[0002] Polyester block copolymers, which have crystalline aromatic polyester units such as polybutylene terephthalate units as hard segments and aliphatic polyether units such as poly(alkylene oxide) glycol as soft segments, are not only excellent in extrusion and injection moldability, but also have high mechanical strength, rubber-like properties such as impact resistance, elastic recovery, flexural fatigue resistance, and flexibility, low- and high-temperature properties, water resistance, and chemical resistance, and are also thermoplastic and easy to mold, so their applications are expanding to fields such as automobile parts, electrical and electronic parts, fibers, and films.

[0003] Theoretically, polyester block copolymers can be made flexible by increasing the mass ratio of the soft segment, but their characteristic good moldability (solidification speed, demoldability) and heat resistance drop sharply. In reality, the surface Shore D hardness is limited to 30, and in terms of flexibility, they are positioned as the hardest elastomer among engineering plastic elastomers and general-purpose elastomers, which limits their application.

[0004] In addition, even if the material is transparent when melted, it becomes cloudy and opaque when cooled and solidified, making it difficult to use in applications requiring translucency or transparency, and it has been particularly difficult to obtain a material that is flexible while having transparency or translucency.

[0005] Techniques for making polyester block copolymers transparent have been investigated. For example, a resin composition made transparent by blending a polyether ester block copolymer with a sodium salt of a carboxylic acid (see, for example, Patent Document 1) and a resin composition made transparent by blending a polyester block copolymer with a polyether ester block copolymer containing ethylene units and carboxylic acid-containing units, in which the carboxylic acid units are neutralized with metal ions, either alone or together with an alkali metal salt of a carboxylic acid (see, for example, Patent Document 2) have been proposed.

[0006] According to these conventional examples, it is certainly possible to obtain resin compositions having higher light transmission and transparency than conventional polyester block copolymers, but on the other hand, the flexibility is insufficient.

[0007] Known conventional attempts to improve the flexibility of polyester block copolymers include a composition consisting of a hydrogenated derivative of a styrene-butadiene block copolymer, a rubber softener, and a polyester elastomer (see, for example, Patent Document 3), and a composition in which a thermoplastic polyester elastomer is blended with a hydrogenated diene copolymer and a plasticizer (see, for example, Patent Document 4).

[0008] According to these conventional examples, by blending a styrene-butadiene block copolymer and a rubber softener or a hydrogenated diene copolymer and a plasticizer with a polyester block copolymer, it is possible to obtain a resin composition that is softer than the conventional polyester block copolymers, but it is not possible to obtain a resin composition that is transparent or translucent.

[0009] On the other hand, in order to obtain a transparent and flexible polyester block copolymer, a composition has been proposed in which a styrene-based elastomer obtained by hydrogenating a polyester block copolymer is blended with an ethylene-based copolymer having a metal carboxylate group in the side chain and / or an alkali metal salt of a carboxylic acid and / or an alkali metal salt of an organic phosphate compound (see, for example, Patent Document 5), and a composition has been proposed in which a styrene-based elastomer, a softener, a thermoplastic polyester block copolymer, and an ionomer are blended (see, for example, Patent Document 6). [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Unexamined Patent Publication No. 52-4549 [Patent Document 2] Japanese Patent Application Publication No. 10-182954 [Patent Document 3] JP-A-1-193352 [Patent Document 4] Japanese Patent Application Publication No. 4-323250 [Patent Document 5] JP 2004-143352 A [Patent Document 6] JP 2016-79226 A Summary of the Invention [Problem to be solved by the invention]

[0011] The resin compositions disclosed in Patent Documents 5 and 6 are indeed flexible and highly transparent, but the transparency (haze value) is insufficient, making it difficult to apply them to components that require excellent appearance. Furthermore, Patent Document 6 has limitations, such as the fact that a specific softener must be blended in order to obtain a thermoplastic elastomer resin composition that is flexible and highly transparent.

[0012] An object of the present invention is to provide a thermoplastic elastomer resin composition which is flexible, has excellent transparency, has a good feel and an excellent appearance. [Means for solving the problem]

[0013] The present inventors focused on styrene-butadiene block copolymers. Specifically, they focused on styrene-ethylene-butylene-styrene (SEBS) block copolymers and their styrene content, and found that a thermoplastic with flexibility and excellent transparency can be obtained by using SEBS with a styrene content of less than 25 wt%, a specific polyester block copolymer, and an ethylene copolymer having an alkali metal salt of carboxylic acid and / or a metal salt of carboxylic acid in the side chain.

[0014] As a result of intensive research into achieving the above object, the present inventors have come to propose the following invention. That is, the aspects of the present invention are as follows. (1) A thermoplastic elastomer resin composition comprising 10 to 95 mass% of a polyester block copolymer (A) having as its main components 10 to 50 mass% of a high melting point crystalline polymer segment (a) composed of a crystalline aromatic polyester unit and 90 to 50 mass% of a low melting point polymer segment (b) composed of an aliphatic polyether unit and / or an aliphatic polyester unit, and 90 to 5 mass% of a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less, in combination with 0.01 to 3 mass parts of an alkali metal salt of a carboxylic acid (C) and / or 0.2 to 20 mass parts of an ethylene copolymer (D) having a carboxylate metal salt in a side chain, the composition having a haze value (cloudiness) of 60% or less as measured on a 2 mm thick sheet. (2) The thermoplastic elastomer resin composition according to (1), further comprising 1 to 100 parts by mass of a softener (E) per 100 parts by mass of the total of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25% by mass or less. (3) The thermoplastic elastomer resin composition according to (1), characterized in that the surface hardness measured according to the method described in JIS K7215 is 90A or less. (4) A molded article made of the thermoplastic elastomer resin composition according to any one of (1) to (3). Effect of the Invention

[0015] According to the present invention, it is possible to provide a thermoplastic elastomer resin composition which is flexible, has excellent transparency, has a good feel and an excellent appearance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described in detail below.

[0017] The thermoplastic elastomer resin composition of the present invention contains a polyester block copolymer (A) mainly composed of 10 to 50 mass% of a high melting point crystalline polymer segment (a) made of a crystalline aromatic polyester unit and 90 to 50 mass% of a low melting point polymer segment (b) made of an aliphatic polyether unit and / or an aliphatic polyester unit. The high melting point crystalline polymer segment (a) of the polyester block copolymer (A) used in the thermoplastic elastomer resin composition of the present invention is a polyester formed mainly from an aromatic dicarboxylic acid or its ester-forming derivative, and a diol or its ester-forming derivative. Specific examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, naphthalene-2,6-dicarboxylic acid, naphthalene-2,7-dicarboxylic acid, anthracene dicarboxylic acid, diphenyl-4,4'-dicarboxylic acid, diphenoxyethane dicarboxylic acid, 4,4'-diphenyl ether dicarboxylic acid, 5-sulfoisophthalic acid, and sodium 3-sulfoisophthalate. Primarily, aromatic dicarboxylic acids are used, but if necessary, a part of the aromatic dicarboxylic acids may be replaced with alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, cyclopentanedicarboxylic acid, 4,4'-dicyclohexyldicarboxylic acid, etc., and aliphatic dicarboxylic acids such as adipic acid, succinic acid, oxalic acid, sebacic acid, dodecanedioic acid, dimer acid, etc. Of course, ester-forming derivatives of dicarboxylic acids, such as lower alkyl esters, aryl esters, carbonate esters, and acid halides, can also be used equally well.

[0018] Specific examples of the diol include diols having a molecular weight of 400 or less, such as aliphatic diols such as 1,4-butanediol, ethylene glycol, trimethylene glycol, pentamethylene glycol, hexamethylene glycol, neopentyl glycol, and decamethylene glycol, alicyclic diols such as 1,1-cyclohexanedimethanol, 1,4-dicyclohexanedimethanol, and tricyclodecane dimethanol, and xylylene glycol. Bis(p-hydroxy)diphenyl, Bis(p-hydroxy)diphenylpropane, 2, 2'-Bis[4-(2-hydroxyethoxy)phenyl]propane, bis[4-(2-hydroxy 1,1-bis[4-(2-hydroxyethoxy)phenyl]sulfone, )phenyl]cyclohexane, 4,4'-dihydroxy-p-terphenyl, 4,4'- Aromatic diols such as dihydroxy-p-quaterphenyl are preferred. The acetyl group may also be used in the form of an ester-forming derivative, such as an acetylated form or an alkali metal salt. obtain.

[0019] These dicarboxylic acids, derivatives thereof, diol components and derivatives thereof may be used in combination of two or more kinds.

[0020] A preferred example of the high melting point crystalline polymer segment (a) is a polybutylene terephthalate unit derived from terephthalic acid and / or dimethyl terephthalate and 1,4-butanediol. Also preferably used is one consisting of a polybutylene terephthalate unit derived from terephthalic acid and / or dimethyl terephthalate and a polybutylene isophthalate unit derived from isophthalic acid and / or dimethyl isophthalate and 1,4-butanediol.

[0021] The low melting point polymer segment (b) of the polyester block copolymer (A) used in the thermoplastic elastomer resin composition of the present invention is an aliphatic polyether and / or an aliphatic polyester. Specific examples of the aliphatic polyether include poly(ethylene oxide) glycol, poly(propylene oxide) glycol, poly(tetramethylene oxide) glycol, poly(hexamethylene oxide) glycol, a copolymer of ethylene oxide and propylene oxide, an ethylene oxide adduct of poly(propylene oxide) glycol, and a copolymer of ethylene oxide and tetrahydrofuran.

[0022] Specific examples of aliphatic polyesters include poly(ε-caprolactone), polyenantholactone, polycaprylolactone, and polybutylene adipate. Among these, poly(tetramethylene oxide) glycol and / or an ethylene oxide adduct of poly(propylene oxide) glycol and / or a copolymer of ethylene oxide and tetrahydrofuran are preferred. The number average molecular weight of these low melting point polymer segments in the copolymerized state is preferably about 300 to 6000.

[0023] The copolymerization amount of the low melting point polymer segment (b) in the polyester block copolymer (A) used in the thermoplastic elastomer resin composition of the present invention is usually 10 to 90 mass %, preferably 20 to 85 mass %, and more preferably 40 to 80 mass %.

[0024] The polyester block copolymer (A) used in the thermoplastic elastomer resin composition of the present invention can be produced by a known method. Specific examples of this production method include a method of transesterifying a lower alcohol diester of a dicarboxylic acid, an excess amount of a low-molecular-weight glycol, and a low-melting polymer segment component in the presence of a catalyst and polycondensing the resulting reaction product, a method of esterifying a dicarboxylic acid, an excess amount of a glycol, and a low-melting polymer segment component in the presence of a catalyst and polycondensing the resulting reaction product, a method of preparing a high-melting crystalline segment in advance, adding a low-melting segment component to it, and randomizing it by transesterification, and a method of connecting a high-melting crystalline segment and a low-melting polymer segment with a chain linking agent. Furthermore, when poly(ε-caprolactone) is used for the low-melting polymer segment, any method may be used, such as an addition reaction of ε-caprolactone monomer to a high-melting crystalline segment.

[0025] The thermoplastic elastomer resin composition of the present invention contains a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less. The styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less used in the thermoplastic elastomer resin composition of the present invention is obtained by hydrogenating a styrene-based block copolymer formed from a block consisting of an aromatic vinyl monomer and a block consisting of a conjugated diene.

[0026] Specific examples of the aromatic vinyl monomer include styrene, α-methylstyrene, vinyltoluene, p-methylstyrene, pt-butylstyrene, o-ethylstyrene, and o,p-dichlorostyrene.

[0027] Specific examples of the conjugated diene include butadiene, butadiene / isoprene copolymer, 2,3-dimethyl-1,3-butadiene, etc. Among these, butadiene is preferable.

[0028] The styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less used in the thermoplastic elastomer resin composition of the present invention has a styrene monomer content of 25 wt% or less in the block copolymer. The content is preferably 20 wt% or less, more preferably 19 wt% or less. The content is preferably 5 wt% or more, more preferably 10 wt% or more, and most preferably 14 wt% or more. SEBS having a styrene content of more than 25 wt% has different compatibility and refractive index from polyester block copolymers, resulting in reduced transparency.

[0029] The styrene content in the block copolymer can be measured by a method based on the IR method described in JIS K6239 (published in 2007) or a known method.

[0030] The styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less used in the thermoplastic elastomer resin composition of the present invention may be modified. The modification is carried out by a carboxyl group-containing unsaturated compound or an acid anhydride-containing unsaturated compound, or an epoxy group-containing monomer. Specific examples of the carboxyl group-containing unsaturated compound include acrylic acid, methacrylic acid, crotonic acid, cinnamic acid, itaconic acid, and maleic acid. Specific examples of the acid anhydride-containing unsaturated compound include maleic anhydride, itaconic anhydride, chloromaleic anhydride, citraconic anhydride, butenyl succinic anhydride, and tetrahydrophthalic anhydride. Specific examples of the epoxy group-containing monomer include glycidyl methacrylate, glycidyl acrylate, vinyl glycidyl ether, and glycidyl ether of hydroxyalkyl (meth)acrylate.

[0031] In the thermoplastic elastomer resin composition of the present invention, 90 to 5 mass%, preferably 85 to 7 mass%, more preferably 80 to 10 mass%, and most preferably 60 to 10 mass% of styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less is blended with 10 to 95 mass% of polyester block copolymer (A). If the blending amount of styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less is less than the above range, flexibility, etc. are insufficient, and if it exceeds the above range, heat resistance, chemical resistance, moldability, etc. are insufficient, which is not preferable.

[0032] The thermoplastic elastomer resin composition of the present invention contains an alkali metal salt of a carboxylic acid (C) and / or an ethylene copolymer (D) having a metal carboxylate group on the side chain.

[0033] The inclusion of an alkali metal salt of a carboxylic acid (C), which is one of the components used in the thermoplastic elastomer resin composition of the present invention, can improve transparency. Preferably, it is an aliphatic carboxylic acid metal salt, more preferably, it is an alkali metal salt of an aliphatic carboxylic acid having 10 or more carbon atoms, and even more preferably, it is an alkali metal salt of an aliphatic carboxylic acid having 10 to 20 carbon atoms. An alkali metal salt of an aliphatic carboxylic acid having 9 or less carbon atoms is preferable because it can improve transparency with a small amount of incorporation, but since the carbon chain is short, it may cause bleeding out during heat treatment. An aliphatic carboxylic acid is a compound in which a carboxyl group is attached to a linear or branched aliphatic group, and may have an unsaturated group, an alicyclic group, an aromatic group, or other substituents such as a hydroxyl group or a phosphate ester group in a part of the bond.

[0034] Of the aliphatic carboxylic acids, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, etc. are preferred, and of the alkali metal salts, sodium salts and potassium salts are preferred in terms of solubility in polyester elastomers and good crystal nucleation properties.

[0035] The amount of the alkali metal salt of carboxylic acid (C) is preferably 0.01 to 3 parts by mass per 100 parts by mass of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less. The amount of the alkali metal salt of carboxylic acid (C) added is more preferably 0.05 to 2 parts by mass, and even more preferably 0.1 to 1 part by mass.

[0036] If the amount of the alkali metal salt of carboxylic acid (C) is less than 0.01 parts by mass, the light transmittance and transparency are insufficient, and if it exceeds 3 parts by mass, the amount of gas generated during processing increases, which may affect moldability. Note that the alkali metal salt of carboxylic acid (C) may be used alone or in combination of two or more kinds.

[0037] The ethylene copolymer (D) having a metal carboxylate group in the side chain, which is one of the components of the thermoplastic elastomer resin composition of the present invention, not only improves transparency but also improves compatibility between the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less. The ethylene copolymer (D) having a metal carboxylate group in the side chain is a copolymer of ethylene and an ethylenically unsaturated carboxylic acid such as acrylic acid, methacrylic acid, maleic acid, or fumaric acid, neutralized with an alkali metal ion, an alkaline earth metal ion, or a zinc ion, and is commercially available, for example, as "Surlyn" from DuPont or "Himilan" from Dow Mitsui Polychemicals. Among them, those neutralized with an alkali metal ion such as sodium, potassium, or lithium are preferable.

[0038] The ethylene copolymer (D) having a carboxylate metal salt group in the side chain is blended in an amount of 0.2 to 20 parts by mass per 100 parts by mass of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less, preferably 0.5 to 15 parts by mass, and particularly preferably 1 to 10 parts by mass.

[0039] When the amount of the ethylene copolymer (D) having a metal carboxylate group in the side chain is less than 0.2 parts by mass, the light transmittance and transparency are insufficient, and when it exceeds 20 parts by mass, phase separation occurs, and the mechanical properties and the light transmittance and transparency are thought to be deteriorated.

[0040] The thermoplastic elastomer resin composition of the present invention has a haze value of 60% or less, measured on a sheet having a thickness of 2 mm. If the haze value exceeds 60%, light diffusion is large and transparency is insufficient. The haze value is preferably 55% or less, more preferably 50% or less, and most preferably 40% or less. If the haze value is 40% or less, it can be applied to applications requiring high transparency, such as automobile parts and electric and electronic parts.

[0041] The thermoplastic elastomer resin composition of the present invention preferably has a surface hardness of 90 A or less, as measured according to the method described in JIS K7215. More preferably, the surface hardness is 85 A or less, more preferably 80 A or less, and most preferably 78 A or less. If the surface hardness is 90 A or less, the composition can be adapted to applications requiring high flexibility, such as automotive interior applications, electronic and electrical applications, grips, cushions, and covers for writing implements, tools, cameras, bicycles, etc.

[0042] The thermoplastic elastomer resin composition of the present invention may further contain a softener (E). By blending a known plasticizer or a known rubber compounding oil as the softener (E), it is possible to improve flexibility and melt fluidity while maintaining translucency and transparency. The plasticizer has good compatibility with the polyester block copolymer (A), and the rubber compounding oil has good compatibility with the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less.

[0043] Specific examples of plasticizers that may be used in the thermoplastic elastomer resin composition of the present invention include phthalate ester plasticizers such as dioctyl phthalate, dibutyl phthalate, diethyl phthalate, butyl benzyl phthalate, di-2-ethylhexyl phthalate, diisodecyl phthalate, diundecyl phthalate, and diisononyl phthalate; tricresyl phosphate, triethyl phosphate, tributyl phosphate, tri-2-ethylhexyl phosphate, trimethyl phosphate, and tris-dichloropropyl phosphate; Trimellitate ester plasticizers such as trimellitic acid octyl ester, trimellitic acid isononyl ester, and trimellitic acid isodecyl ester; dipentaerythritol ester plasticizers; fatty acid ester plasticizers such as dioctyl adipate, di-2-ethylhexyl adipate, diisobutyl adipate, dibutyl adipate, diisodecyl adipate, dibutyl diglycol adipate, di-2-ethylhexyl azelate, dioctyl sebacate, and methyl acetyl ricinoleate; Examples of the plasticizer include pyromellitic ester plasticizers such as romellitic acid octyl ester, epoxidized soybean oil, epoxidized linseed oil, and epoxidized fatty acid alkyl ester plasticizers, polyether plasticizers such as adipic acid ether ester, polyether ester, and polyether, and benzoate plasticizers such as diethylene glycol dibenzoate, polypropylene glycol dibenzoate, tripropylene glycol dibenzoate, dipropylene glycol dibenzoate, propylene glycol dibenzoate, dibutylene glycol dibenzoate, neopentyl glycol dibenzoate, glyceryl tribenzoate, pentaerythritol tetrabenzoate, triethylene glycol dibenzoate, polyethylene glycol dibenzoate, and trimethylolethane tribenzoate. Among these, it is preferable to use one or more compounds selected from ether plasticizers, benzoate plasticizers, phthalate plasticizers, trimellitic ester plasticizers, and pyromellitic ester plasticizers. More preferably, it is an ether plasticizer. These plasticizers can be used alone or in combination of two or more kinds.The boiling point of these plasticizers is preferably 200° C. or higher, and more preferably 300° C. or higher. be.

[0044] Specific examples of rubber compounding oils that may be used in the thermoplastic elastomer resin composition of the present invention include mineral oil compounding oils such as naphthenic oils and paraffinic oils, and synthetic resin compounding oils such as polybutene and low molecular weight polybutadiene, among which paraffinic oils and / or naphthenic oils are preferably used. These rubber compounding oils can be used alone or in combination of two or more. The boiling point of these rubber compounding oils is preferably 200°C or higher, more preferably 300°C or higher. be.

[0045] In the present invention, when the softener (E) is used, it is contained in an amount of 1 to 100 parts by mass per 100 parts by mass of the total of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less. It is preferably 1 to 50 parts by mass, and more preferably 1 to 10 parts by mass. If it is less than 1 part by mass, the imparting of flexibility and melt fluidity is small, and if it is more than 100 parts by mass, there is a possibility that problems will occur in the appearance due to bleeding out, etc.

[0046] The thermoplastic elastomer resin composition of the present invention may contain a fatty acid amide compound in order to suppress the occurrence of blocking or surface peeling while maintaining light transmission and transparency.

[0047] The fatty acid amide compound that may be used in the thermoplastic elastomer resin composition of the present invention is a compound obtained by the reaction of a fatty acid with an amine compound, and examples thereof include one or more compounds selected from alkylenebis-higher fatty acid amide compounds and carboxylic acid amide waxes obtained by the reaction of a mixture of a higher aliphatic monocarboxylic acid and a polybasic acid with a diamine. Specific examples of alkylene bis-higher fatty acid amide compounds include monoamide compounds such as oleyl oleic acid amide, stearyl oleic acid amide, and oleyl stearic acid amide, methylene bis-stearic acid amide, methylene bis-oleic acid amide, methylene bis-lauric acid amide, methylene bis-capric acid amide, methylene bis-myristic acid amide, methylene bis-palmitic acid amide, ethylene bis-stearic acid amide, ethylene bis-oleic acid amide, ethylene bis-lauric acid amide, ethylene bis-capric acid amide, ethylene bis-myristic acid amide, and ethylene bis-palmitic acid amide, and other alkylene symmetric bis-higher fatty acid amides, methylene stearyl oleyl bisamide, methylene stearyl lauryl bisamide, methylene palmitoleyl bisamide, ethylene stearyl oleyl bisamide, ethylene stearyl lauryl bisamide, and ethylene palmitoleyl bisamide.Also, it may be a mixture of alkylene symmetric bis-higher fatty acid amide and alkylene asymmetric bis-higher fatty acid amide compound.

[0048] When these fatty acid amide compounds are used in the thermoplastic elastomer resin composition of the present invention, the amount is 0.01 to 5 parts by mass, preferably 0.05 to 3 parts by mass, per 100 parts by mass in total of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt % or less.

[0049] In the thermoplastic elastomer resin composition of the present invention, one or more selected from a hindered phenol radical scavenger, a peroxide decomposer, and a light stabilizer can be further blended to improve resistance to discoloration caused by heat or light while maintaining transparency. The hindered phenol radical scavenger used here is preferably a hindered phenol compound having a molecular weight of 500 or more. The peroxide decomposer is preferably a phosphite compound and / or a thioether compound. The phosphite compound is more preferably one having two or more phosphorus atoms in the molecule. The light stabilizer is preferably a benzotriazole compound, a benzophenone compound, or a hindered amine compound. These may be used alone, but it is more preferable to use a combination of an ultraviolet absorber such as a benzotriazole compound or a benzophenone compound with a hindered amine light stabilizer.

[0050] When these antioxidants or light stabilizers are used, the amount is 0.01 to 5 parts by mass, and preferably 0.1 to 3 parts by mass, each per 100 parts by mass of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt % or less.

[0051] The thermoplastic elastomer resin composition of the present invention can be blended with various other additives, including resins other than those of the present invention, flame retardants, inorganic fillers, stabilizers, and antioxidants that are widely used as additives to thermoplastic elastomers, within the range that does not impair the characteristics of the present invention (haze value of 60% or less measured on a sheet with a thickness of 2 mm).

[0052] Other additives that can be added include color pigments, inorganic and organic fillers, coupling agents, tackiness improvers, quenchers, stabilizers such as metal deactivators, and polyfunctional glycidyl group-containing styrene-based polymers.

[0053] The method for producing the thermoplastic elastomer resin composition of the present invention is not particularly limited, and examples of the method that can be used appropriately include a method in which a raw material containing a polyester block copolymer, a styrene-ethylene-butylene-styrene (SEBS) block copolymer having a styrene content of 25 wt % or less, an alkali metal salt of carboxylic acid and / or an ethylene-based copolymer having a carboxylate metal salt in its side chain and other additives is fed into a screw-type extruder and melt-kneaded, or a method in which a polyester block copolymer is first fed into a screw-type extruder and melted, and then a styrene-ethylene-butylene-styrene (SEBS) block copolymer having a styrene content of 25 wt % or less, an alkali metal salt of carboxylic acid and / or an ethylene-based copolymer having a carboxylate metal salt in its side chain and other additives are fed into the screw-type extruder from another feed port and kneaded.

[0054] The thermoplastic elastomer resin composition of the present invention is molded by injection molding, extrusion molding, etc., and gives molded products that are flexible, transparent or translucent, have excellent rubber elasticity such as impact resilience, high mechanical properties such as breaking strength and breaking elongation, and have beautiful surface appearance. Therefore, it is useful for various molded products for automobiles, electronic and electric devices, precision instruments, and general consumer goods. It is also suitable for grips, tubes, packings, gaskets, cushions, films, skins, and sheets. The molded product of the present invention is made of the thermoplastic elastomer resin composition of the present invention.

[0055] It is also useful to obtain a composite molded product by laminating a layer made of the thermoplastic elastomer resin composition of the present invention and a hard resin layer. The hard resin constituting the hard resin layer is not particularly limited as long as it maintains the rigidity of the composite molded product and has the desired mechanical strength. Specific examples of the hard resin include polycarbonate resin, polyester resin, polyamide resin, polyacetal resin, ABS resin, acrylic resin, styrene resin, and polyolefin resin, and among these, polycarbonate resin, ABS resin, PBT resin, PCTA resin, and polypropylene resin are preferred.

[0056] The composite molded article is produced by a co-extrusion molding method or a multi-color injection molding method such as two-color molding. The thermoplastic elastomer resin composition of the present invention has excellent adhesion to these hard resins. These composite molded articles can be preferably used for various housings, antenna covers, connectors, grips, rollers, casters, hoses, multi-layer tubes, etc. EXAMPLES

[0057] The effects of the present invention will be described below with reference to examples. In the examples, % and parts are all based on mass unless otherwise specified. The physical properties shown in the examples were measured as follows.

[0058] Melting point Using a differential scanning calorimeter (DSC Q1000 manufactured by TA Instruments), the top temperature of the melting peak when heated at a temperature increase rate of 10° C. / min in a nitrogen gas atmosphere was measured.

[0059] Surface hardness (Shore A scale) Measurements were performed in accordance with JIS K-7215.

[0060] Total light transmittance and haze value Using an electric injection molding machine (NEX-1000) manufactured by Nissei Plastics Industries Co., Ltd., test pieces measuring 125 mm x 75 mm and 2 mm thick were prepared at 220°C (mold temperature: 40°C). The surface roughness of the test pieces was measured using a VK-9700 manufactured by KEYENCE Corporation and found to be 0.46 μm. The test pieces were then measured using a DIRECT READING HAZEMETER manufactured by Toyo Seiki Seisakusho Co., Ltd. in accordance with ASTM D1003.

[0061] Melt Viscosity (MFR) Measured according to ASTM D-1238 at 210°C and a load of 2160g.

[0062] Reference example Production of polyester block copolymer (A-1) 234 parts of terephthalic acid, which is a high melting point crystalline polymer segment made of crystalline aromatic polyester, 754 parts of poly(tetramethylene oxide) glycol with a number average molecular weight of about 2000, which is a low melting point polymer segment made of aliphatic polyether units and / or aliphatic polyester units, 228 parts of 1,4-butanediol, and 0.2 parts of titanium tetrabutoxide were charged into a reaction vessel equipped with a helical ribbon type stirring blade, and heated at 190 to 225 ° C for 3 hours to carry out an esterification reaction while distilling the reaction water out of the system. After adding 0.5 parts by mass of "IRGANOX" 1330 (a hindered phenol radical scavenger manufactured by BASF) to 100 parts by mass of polyester block copolymer component, the temperature was raised to 245 ° C, and then the pressure in the system was reduced to 0.2 mmHg over 50 minutes, and polymerization was carried out under those conditions for 3 hours and 30 minutes. The obtained polymer was discharged into water in the form of a strand, and cut into pellets.

[0063] Production of polyester block copolymer (A-2) 278 parts of terephthalic acid, which is a high melting point crystalline polymer segment made of crystalline aromatic polyester, 686 parts of poly(tetramethylene oxide) glycol with a number average molecular weight of about 1400, which is a low melting point polymer segment made of aliphatic polyether units and / or aliphatic polyester units, 316 parts of 1,4-butanediol, and 0.1 parts of titanium tetrabutoxide were charged together in a reaction vessel equipped with a helical ribbon type stirring blade, and heated at 190 to 225 ° C for 3 hours to perform an esterification reaction while distilling the reaction water out of the system. After adding 0.1 parts by mass of “IRGANOX” 1330 (a hindered phenol radical scavenger manufactured by BASF) to 100 parts by mass of polyester block copolymer component, the temperature was raised to 245 ° C, and then the pressure in the system was reduced to 0.2 mmHg over 50 minutes, and polymerization was performed under those conditions for 2 hours and 45 minutes. The obtained polymer was discharged in the form of a strand into water and cut into pellets.

[0064] Table 1 shows the composition and properties of A-1 and A-2. In the table, PTMG stands for poly(tetramethylene oxide) glycol, the numbers for the low melting point polymer segment, and BD stands for 1,4-butanediol.

[0065] [Table 1]

[0066] Examples 1 to 10 The polyester block copolymer (A-1) or (A-2) obtained in the Reference Examples was mixed with a styrene-ethylene-butylene-styrene (SEBS) block copolymer having a styrene content of 25 wt% or less ("Tuftec" H1521, manufactured by Asahi Kasei Corporation, styrene content 18 wt%) (B-1) or ("Tuftec" H1521, manufactured by Asahi Kasei Corporation, styrene content 12 wt%) (B-3), an alkali metal salt of a carboxylic acid (sodium stearate (sodium stearate) manufactured by Nitto Kasei Kogyo Co., Ltd.) (C-1) or (NS-3A (lauric acid, manufactured by Nitto Kasei Kogyo Co., Ltd.)) (C-2). Sodium) (C-2), KS-3 (potassium laurate) (C-3), ethylene copolymer with sodium carboxylate group in the side chain (DuPont's "Sarlyn" AD8610) (D-1), softener (ether-based plasticizer, Sanyo Chemical Industries Co., Ltd.'s "Sunflex" EB-400) (E-1), or paraffin-based oil, Idemitsu Kosan Co., Ltd.'s "Diana Process Oil" PW-100G) (E-2) were dry-blended in the ratios shown in Table 2, melt-kneaded using a twin-screw extruder with a cylinder diameter of 45 mmφ, and then pelletized. The pellets were dried at 80°C for 3 hours, and then test pieces of 125 mm x 75 mm and 2 mm thick were prepared using Nissei Plastics' electric injection molding machine (NEX-1000) at 220°C (mold temperature: 40°C). The total light transmittance and haze value of the obtained sheet having a thickness of 2 mm were measured, and the surface hardness was also measured according to JIS K-7215.

[0067] Comparative Examples 1-2 The polyester block copolymer (A-1) or (A-2) obtained in the reference examples was dry-blended with a styrene-ethylene-butylene-styrene (SEBS) block copolymer having a styrene content of 25 wt% or less (Asahi Kasei Corporation's "Tuftec" H1521, styrene content 18 wt%) (B-1) or a styrene-ethylene-butylene-styrene (SEBS) block copolymer having a styrene content of more than 25 wt% (Asahi Kasei Corporation's "Tuftec" H1041, styrene content 30 wt%) (B-2) and an alkali metal salt of a carboxylic acid (Nitto Kasei Corporation's NS-3A (sodium laurate)) (C-2) in the mixing ratios shown in Table 2, and the mixture was melt-kneaded and pelletized using a twin-screw extruder with a cylinder diameter of 45 mmφ. The pellets were dried at 80°C for 3 hours, and then a test piece measuring 125 mm x 75 mm and 2 mm thick was produced at 220°C (mold temperature: 40°C) using an electric injection molding machine (NEX-1000) manufactured by Nissei Plastic Industrial Co., Ltd. The total light transmittance and haze value were measured using the obtained 2 mm thick sheet. The surface hardness was also measured according to JIS K-7215.

[0068] [Table 2]

[0069] [Table 3]

[0070] As is clear from Examples 1 to 10 in Tables 2 and 3, a polyester elastomer resin composition containing 10 to 95 mass% of a polyester block copolymer (A) having as its main components 10 to 50 mass% of a high melting point crystalline polymer segment (a) composed of crystalline aromatic polyester units and 90 to 50 mass% of a low melting point polymer segment (b) composed of an aliphatic polyether unit and / or an aliphatic polyester unit, and 90 to 5 mass% of a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less, and blended with 0.01 to 3 mass parts of an alkali metal salt of a carboxylic acid (C) and / or 0.2 to 20 mass parts of an ethylene copolymer (D) having a carboxylate metal salt group in a side chain, for a total of 100 mass parts, is flexible, has excellent transparency, has a good touch, and has excellent appearance.

[0071] From Comparative Example 1, a thermoplastic elastomer resin composition containing a polyester block copolymer (A) and a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less, but not containing an alkali metal salt of a carboxylic acid (C) or an ethylene copolymer (D) having a carboxylate metal salt group in a side chain, has poor transparency. Also, from Comparative Example 2, even if 0.01 to 3 parts by mass of an alkali metal salt of a carboxylic acid is blended with 10 to 95% by mass of a polyester block copolymer and 90 to 5% by mass of a styrene-ethylene-butylene-styrene (SEBS) block copolymer, the transparency is reduced because of differences in compatibility and refractive index with the polyester block copolymer when the styrene content of the styrene-ethylene-butylene-styrene (SEBS) block copolymer is more than 25%.

[0072] [Table 4]

[0073] As is clear from Examples 6, 8 and 9 in Table 4, a polyester elastomer resin composition containing 10 to 95 mass% of a polyester block copolymer (A) having as its main components 10 to 50 mass% of a high melting point crystalline polymer segment (a) composed of a crystalline aromatic polyester unit and 90 to 50 mass% of a low melting point polymer segment (b) composed of an aliphatic polyether unit and / or an aliphatic polyester unit, and 90 to 5 mass% of a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less, 0.01 to 3 mass parts of an alkali metal salt of a carboxylic acid (C) and / or 0.2 to 20 mass parts of an ethylene copolymer (D) having a carboxylate metal salt group in a side chain, and 1 to 100 mass parts of a softener (E) is not only more flexible and excellent in transparency, good touch and excellent appearance, but also has a high MFR and high fluidity. [Industrial Applicability]

[0074] The thermoplastic elastomer resin composition of the present invention is useful as a thermoplastic elastomer material having excellent flexibility, transparency, good touch and appearance compared to conventional polyester elastomer resin compositions. For example, it is expected to be used in automobile interior applications, electronic and electrical applications, grips, cushions, and covers for writing implements, tools, cameras, bicycles, etc.

Claims

1. 1. A thermoplastic elastomer resin composition comprising 10 to 95 mass% of a polyester block copolymer (A) comprising as main components 10 to 50 mass% of a high melting point crystalline polymer segment (a) composed of crystalline aromatic polyester units and 90 to 50 mass% of a low melting point polymer segment (b) composed of an aliphatic polyether unit and / or an aliphatic polyester unit, and 90 to 5 mass% of a styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 wt% or less, in combination with 0.01 to 3 mass parts of a carboxylic acid alkali metal salt (C) and / or 0.2 to 20 mass parts of an ethylene copolymer (D) having a carboxylate metal salt in a side chain, the composition having a haze value (cloudiness) of 60% or less as measured on a 2 mm thick sheet.

2. The thermoplastic elastomer resin composition according to claim 1, further comprising 1 to 100 parts by mass of a softener (E) per 100 parts by mass in total of the polyester block copolymer (A) and the styrene-ethylene-butylene-styrene (SEBS) block copolymer (B) having a styrene content of 25 mass% or less.

3. 2. The thermoplastic elastomer resin composition according to claim 1, wherein the surface hardness measured according to the method described in JIS K7215 is 90A or less.

4. A molded article comprising the thermoplastic elastomer resin composition according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Polyester elastomer composition

    JP1977004549A

  • Thermoplastic elastomer composition

    JP1989193352A

  • Thermoplastic elastomer composition

    JP1992323250A

  • Polyester elastomer resin composition

    JP1998182954A

  • Thermoplastic elastomer resin composition and molded product

    JP2004143352A